The effect of Metabolic Syndrome on Exercise Performance in American Football Players From a Mexican University - Morales Elizondo, Dulce Edith; Morales Corral, Pedro Gualberto; Sámano Pérez, Elfega; Sepúlveda Sepúlveda, Rosalinda; Pérez, Héctor E.; Barrera Flores, Francisco Jesús; Rizo Belloso, Emanuel (2019)
eventy six players were included in the study, thirteen had MetSyn (21.7±1.5 yrs) and sixty three were not diagnosed with MetSyn (21.8±1.5 yrs). In order to establish a statistical significance between the physical performance and MetSyn, the data was analyzed in two different ways: With MetSyn (WMS) or absence of MetSyn (AMS) and by groups of similarity of Body Mass and type of execution in the field Group 1 Offensive and Linemen (OL and DL) and Tight ends (TE). Group 2 Running Backs (RB), Linebackers (LB) and Quarterbacks (QB). Group 3 Wide Receivers (WR), Kickers (K), Strong Safeties (SS) and Cornerbacks (CB). The physical performance tests that were measured were: Maximum strength, explosive strength, Isometric hand strength, muscular resistance, power of upper and lower body, lumbar flexibility, agility, speed and cardiovascular resistance.